2022
DOI: 10.3389/fcvm.2022.871654
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Outcomes of Ablation With Vein of Marshall Ethanol Infusion vs. Ablation Alone in Patients With Atrial Fibrillation: A Meta-Analysis

Abstract: BackgroundThe long-term outcomes of ablation with vein of Marshall ethanol infusion (VOM-ABL) compared with ablation alone in patients with atrial fibrillation (AF) remains elusive. We aimed to explore whether VOM-ABL showed better long-term benefits and screen the potential determinants of outcome impact of VOM-ABL procedure.MethodsPubMed, Cochrane Library, Web of Science, and Embase were searched up to 1st September 2021. Studies comparing the long-term (one-year or longer) outcomes between VOM-ABL and ablat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…[20] with twenty-six studies including a total of 57,993 patients suggested that male gender, chronice kidney disease, previous myocardial infarction, native QRS duration, and paced QRS duration were identified to be the most important risk factors for pacing induced cardiomyopathy. Moreover, our previous studies also revealed that high-volume center (also meant a high sample size for a key technique) representing a relatively advanced operational team, was significantly associated with a better effacacy and comparable safety[7, 21]. Whereas, very few studies have reported the potential risk factors for the potential pacing induced new-onset AF.…”
Section: Discussionmentioning
confidence: 99%
“…[20] with twenty-six studies including a total of 57,993 patients suggested that male gender, chronice kidney disease, previous myocardial infarction, native QRS duration, and paced QRS duration were identified to be the most important risk factors for pacing induced cardiomyopathy. Moreover, our previous studies also revealed that high-volume center (also meant a high sample size for a key technique) representing a relatively advanced operational team, was significantly associated with a better effacacy and comparable safety[7, 21]. Whereas, very few studies have reported the potential risk factors for the potential pacing induced new-onset AF.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a randomized study demonstrated reduced rates of recurrent AT (and AF) on follow-up in those receiving adjunct VoM ethanol infusion during ablation for persistent AF (41), with peri-mitral block identified as a significant determinant of outcome (42). A recently published meta-analysis of the technique confirmed these findings with greater freedom from recurrent AT and AF with adjunct VoM ethanol infusion compared with ablation alone in patients with AF (43). Epicardial connections across roof lines utilizing the septopulmonary bundle, which again may be insulated by fat, have been demonstrated to be a common cause of failure to achieve roof line block (44).…”
Section: Epicardial Connections and Novel Techniquesmentioning
confidence: 91%
“…A subgroup analysis was also performed according to our previous reported methods 13 . A total of seven confounding factors were screened, including study region (Asian and non‐Asian), numbers of patients with diabetes (≥10 000 and < 10 000), age (≥60 years and < 60 years), gender (≥50% male and <50% male), types of diabetes (type 2 diabetes and type 1 diabetes), adjustment of diabetes duration (Yes and No), adjustment of baseline HbA1c (Yes and No), and follow‐up time (≥5 years and <5 years).…”
Section: Methodsmentioning
confidence: 99%